NILAI RERATA SINGLE BREATH COUNT TEST DAN PEAK EXPIRATORY FLOW RATE PADA PASIEN SKOLIOSIS DI RSUD ULIN BANJARMASIN - Hasna, Usratul; Hayati, Azka; Asnawati, Asnawati; Siddik, Muhammad; Marisa, Dona (Universitas Lambung Mangkurat, 2024)
Abstract: Scoliosis is a three-dimensional vertebral disorder in the form of an abnormal curvature laterally affecting one or more segments of the thoracolumbar vertebral column by forming the letter